-59=3(x-3)+4(5x-1)

Simple and best practice solution for -59=3(x-3)+4(5x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -59=3(x-3)+4(5x-1) equation:



-59=3(x-3)+4(5x-1)
We move all terms to the left:
-59-(3(x-3)+4(5x-1))=0
We calculate terms in parentheses: -(3(x-3)+4(5x-1)), so:
3(x-3)+4(5x-1)
We multiply parentheses
3x+20x-9-4
We add all the numbers together, and all the variables
23x-13
Back to the equation:
-(23x-13)
We get rid of parentheses
-23x+13-59=0
We add all the numbers together, and all the variables
-23x-46=0
We move all terms containing x to the left, all other terms to the right
-23x=46
x=46/-23
x=-2

See similar equations:

| 4^x=292 | | 1/2x−12=−20 | | 4.5=1.5-x | | −38−8x=22−5x | | 24÷4(24÷2)=x | | r/5+6=10 | | −14=1.5x−2 | | 7/2x+1/2x=131/2+9.2x | | -76+6j=-34 | | 6-3n=54 | | 6x+3=5x+912 | | -2q+2=4 | | 6-3n=-54 | | 7c-9=13c+37 | | 10/3x+5=11 | | e+(4)3/4=-3.1 | | y/2+7=20 | | 0.19x-0.6=0.15x | | (x-3)^2=4|x-3| | | 6x+3=5x+912) | | 6t+8=2t+40 | | 10+4+x=4+11x | | e+4(3)/(4)=-3.1 | | 7(8-6x)=350 | | 2x^2|1=23 | | 2y-3(4y)=100 | | 2x^21=23 | | -4.9+2x=7.1 | | 350=7(8−6x) | | 3=50x | | –12=4p | | 4=h−2 |

Equations solver categories